Mapping the Process of Translation - Fraser, Janet (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1996)
AbstractThe aim of this article is to consider whether the training of student translators should be product-driven or process-driven. The author briefly comments on why current translation theory sometimes seems unhelpful to trainee and practising translators. Then she presents the findings of two studies of professional translators at work, and finally, from an analysis of the processes professionals engage in, she draws up some principles for a systematic approach to translator training.